Properties of electropolymerised polyaniline thin films obtained from different supporting electrolytes. (3rd September 2017) - Hamza, D. E.; Lahmar, H.; Azizi, A.; Schmerber, G.; Dinia, A.
Abstract : This work reports on the properties of polyaniline (PANI) films electrochemically synthesised onto indium tin oxide (ITO) coated glass substrate from a mixed solution of 0.1 M aniline with three different types of supporting electrolytes: HNO3, H2 SO4 and H3 PO4 . In order to investigate the effect of dopant on the behaviour of polyaniline different techniques have been employed. These characterisations were made using photoelectrochemical, FTIR and Raman spectroscopies, field-emission scanning electron microscopy, UV–vis spectroscopy, diffuse reflectance spectrophotometry and photoluminescence techniques. The potocurent transients show a change of PANI films conductivity from p-type to n-type by changing the supporting electrolytes. The FTIR technique and Raman spectroscopy confirmed the formation of PANI thin film on ITO substrates. The morphology of the electropolymerised PANI thin films is closely related to the supporting electrolytes. Compact and spongy morphologies were observed for PANI films deposited in different supporting electrolytes. The optical measurements show an optical transmittance in the visible region, with variations depending on the nature of electrolytes.